2009
DOI: 10.1523/jneurosci.5569-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Ventral Mesencephalon-Enriched Genes That Regulate the Development of Dopaminergic NeuronsIn Vivo

Abstract: Mesodiencephalic dopaminergic (mDA) neurons are critical for movement control and other physiological activities. However, the molecular mechanisms underlying their development are poorly understood. We aimed to establish the expression profiles of genes involved in this process and unravel genetic programs that control late development of mDA neurons. We compared genome-wide gene expression profiles of developing mouse ventral mesencephalon (VM) using microarrays. We identified a set of genes that show spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 27 publications
2
47
0
Order By: Relevance
“…From 72 hpf on, Id3 expression was gradually down regulated. This up-then-down trend of Id3 expression in zebrafish is consistent with that in mouse VM revealed in our previous microarray data (Yin et al, 2009). These data suggest that Id3 may play a role in early development of DA neurons.…”
Section: Identification Of Genes That Show Restricted Expression In Tsupporting
confidence: 90%
See 4 more Smart Citations
“…From 72 hpf on, Id3 expression was gradually down regulated. This up-then-down trend of Id3 expression in zebrafish is consistent with that in mouse VM revealed in our previous microarray data (Yin et al, 2009). These data suggest that Id3 may play a role in early development of DA neurons.…”
Section: Identification Of Genes That Show Restricted Expression In Tsupporting
confidence: 90%
“…Previously, we found that Fabp7, a fatty acid binding protein, was exclusively expressed in neuroepithelial cells in the VM of mouse embryos in addition to other brain regions (Yin et al, 2009). In zebrafish larvae, Fabp7 mRNA was found to be highly enriched in the hindbrain, especially rhombomere 4, and also diencephalon as well as in the eyes (Figs.…”
Section: Identification Of Genes That Show Restricted Expression In Tmentioning
confidence: 94%
See 3 more Smart Citations